2012
DOI: 10.1083/jcb.201201096
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry for binding and transport by the twin arginine translocation system

Abstract: Stoichiometry determined in this study suggests that the fully loaded and assembled Tat translocase is an ∼2.2-megadalton complex that can individually transport eight precursor proteins or cooperatively transport multimeric precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 53 publications
(89 reference statements)
4
75
0
Order By: Relevance
“…8). Similar considerations apply if multiple substrate-binding sites within the TatBC complex are able to access the same TatA assembly (20,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8). Similar considerations apply if multiple substrate-binding sites within the TatBC complex are able to access the same TatA assembly (20,48).…”
Section: Discussionmentioning
confidence: 99%
“…However, during transport at high substrate concentrations, binding of the next substrate molecule to the TatBC complex might occur before TatA dissociation has started or before it has been fully completed. Under these conditions it is implicit in our model that TatA sites can be reused, as recently suggested (20), or regenerated from a partially disassembled state by reversing the direction of the disassembly equilibrium upon substrate binding (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of the signal peptide triggers assembly of Tha4 (Mori and Cline, 2002). In nontransporting membranes, Tha4 appears to be a homotetramer, whereas in the translocase, it assembles as homooligomers of ;20 to 25 Tha4 protomers (Leake et al, 2008;Dabney-Smith and Cline, 2009;Celedon and Cline, 2012). For this and other reasons, Tha4 (TatA) is thought to form the protein-conducting structure.…”
Section: Introductionmentioning
confidence: 99%
“…cpTatC (TatC) is the primary receptor for the signal peptide (Alami et al, 2003;Gérard and Cline, 2006), although Hcf106 (TatB) also contacts the signal peptide to a lesser extent. Under saturating conditions, each cpTatC within a receptor complex binds a substrate protein (Celedon and Cline, 2012). Kinetic analysis of transport showed that each cpTatC-Hcf106 pair independently transports its bound substrate in an apparently stochastic manner (Celedon and Cline, 2012).…”
Section: Introductionmentioning
confidence: 99%